Dietary pattern and gut microbiota in type 2 diabetes mellitus: A literature review - Martha Pitaloka Putri; Endang Sri Lestari; Diana Nur Afifah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Nutrition has been identified as the primary modifiable factor, and the type of food, macronutrients, and micronutrient composition of the diet have distinct effects on gut microbiota and related metabolites. These effects significantly influence the mechanisms that regulate hyperglycemia and insulin resistance, influencing gut microbiota remodeling and the development of T2DM. This study aimed to gather information on changes in gut microbiota composition (Lactobacillus and Bifidobacterium) and describe the beneficial or detrimental effects, impacts, and outcomes of macronutrients (carbohydrate, protein, and fat) and fiber on gut microbiota composition in T2DM. Nine English articles were obtained from the literature review. Lactobacillus and Bifidobacterium can positively reduce the blood glucose levels. Changes in the gut microbiota and its metabolites, which are influenced by carbohydrate, protein, lipid, and fiber intake, can worsen or decrease biochemical parameters and improve T2DM complications. The conclusion of this literature review is that gut microbiota can be crucial in the future treatment of diabetes mellitus, especially in combination with other therapeutic options.